The Influence of Learning Models Project Based Learning In the subject of Pancasila Education towards Strengthening the Profile of Pancasila Students and Learning Outcomes of Class X Students at SMA Negeri 2 Enrekang - Arifin, Nur Ariska; Sugiati, Andi; Nur, Jumiati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study analyzes the effect of Project Based Learning learning model in strengthening Pancasila Student Profile and improving learning outcomes in Pancasila Education subject in class X of SMA Negeri 2 Enrekang using quantitative method with quasi experiment approach on 66 students from class X.9 and X.10. The results showed that Project Based Learning was significantly more effective than conventional method in strengthening Pancasila Student Profile (average score 3.85 compared to 2.10 with difference 1.710) and improving student learning outcomes (increase in experimental class score from pretest 57.73 to posttest 82.27, while control class from 59.24 to 78.18), supported by t-test result with significance value p = 0.016 (<0.05).